Modeling pore wetting in direct contact membrane distillation—effect of interfacial capillary pressure - S. N. A. Ahmad; Takeshi Matsuura; Takeshi Matsuura; Juhana Jaafar; L. Y. Jiang; A. F. Ismail; M. H. D. Othman; Mukhlis A. Rahman (Frontiers in Membrane Science and Technology)
In this study, we aimed to develop a model for computing direct contact membrane distillation (DCMD) performance, taking into account capillary pressure effects at the liquid–gas interface within membrane pores. We developed a simulation model to investigate how factors such as pore radius, feed/permeate temperature, pressure, and contact angle influenced the distance of liquid intrusion into the pore, the weight flow rate in a single pore, and the temperature at the liquid–gas interface. The model predicted that the permeation rate would decrease with an increase in the feed pressure when the permeate pressure was kept constant and also when the pressure difference between the feed and permeate was kept constant. It also predicted that the permeation rate would increase with an increase in the permeate pressure when the feed pressure was kept constant. The model also indicated that partial pore wetting would be enhanced with an increase in feed pressure when the pore size was as large as 1 μm but would diminish when the pore size was as small as 0.1 μm. According to the model, partial pore wetting diminished with a decrease in the permeate pressure. The model’s predictions were in line with the trends observed in the experimental DCMD flux data by many authors, particularly those regarding the effects of feed and permeate temperature and the effect of contact angle. The model’s predictions were compared with the experimental data recorded in the literature, validating the model’s accuracy.